Predictors of Academic Achievement at Different Levels of Socioeconomic Status - Deveci, Ceyda Çavusoglu; Ersen, Rabia Karatoprak (Canadian Center of Science and Education, 2022)
Success is a concept that is desired by everyone. In the Turkish education system, Anatolian high schools are considered one of the most prestigious schools which accept students via national central exams. The purpose of this study is to reveal indicators explaining the placement into Anatolian high schools, which is an important sign of success, in socioeconomically different regions. Logistic regression analyses were used as a prediction design. Data was collected from the 1049 10th grade high school students in Istanbul. According to findings, the indicators affecting the probability of studying in Anatolian high school differ between the low life quality indexed region (LLQR) and the high life quality indexed region (HLQR). In LLQR GPA, gender, number of people in the household, and mother’s monetary contribution were found as significant indicators. In HLQR GPA, father’s income and mother’s education level were found as significant indicators. These results are discussed using the main theories of educational sociology.
Keywords: 4. Education